Redirecting Specificity of T cells Using the Sleeping Beauty System to Express Chimeric Antigen Receptors by Mix-and-Matching of VL and VH Domains Targeting CD123+ Tumors. - Radhika Thokala; Simon Olivares; Tiejuan Mi; Sourindra Maiti; Drew Deniger; Helen Huls; Hiroki Torikai; Harjeet Singh; Richard E Champlin; Tamara Laskowski; George McNamara; Laurence J N Cooper (PLoS ONE, 2016)
Adoptive immunotherapy infusing T cells with engineered specificity for CD19 expressed on B- cell malignancies is generating enthusiasm to extend this approach to other hematological malignancies, such as acute myelogenous leukemia (AML). CD123, or interleukin 3 receptor alpha, is overexpressed on most AML and some lymphoid malignancies, such as acute lymphocytic leukemia (ALL), and has been an effective target for T cells expressing chimeric antigen receptors (CARs). The prototypical CAR encodes a VH and VL from one monoclonal antibody (mAb), coupled to a transmembrane domain and one or more cytoplasmic signaling domains. Previous studies showed that treatment of an experimental AML model with CD123-specific CAR T cells was therapeutic, but at the cost of impaired myelopoiesis, highlighting the need for systems to define the antigen threshold for CAR recognition. Here, we show that CARs can be engineered using VH and VL chains derived from different CD123-specific mAbs to generate a panel of CAR+ T cells. While all CARs exhibited specificity to CD123, one VH and VL combination had reduced lysis of normal hematopoietic stem cells. This CAR's in vivo anti-tumor activity was similar whether signaling occurred via chimeric CD28 or CD137, prolonging survival in both AML and ALL models. Co-expression of inducible caspase 9 eliminated CAR+ T cells. These data help support the use of CD123-specific CARs for treatment of CD123+ hematologic malignancies.